Tamiya Mini 4WD Borneo Challenge Mukah Cup 2018 - Tang, Hawe Eng (UiTM Sarawak, 2018)
For the very first time, UiTM Sarawak Mukah campus, in collaboration with Frenz Mini 4WD, was proud to be the co-organiser of a well-known event, the Tamiya Mini 4WD Borneo Challenge Mukah Cup 2018. The three-day race was held from 30 March to 1 April 2018 at Dewan Sri Balau, UiTM Sarawak Mukah Campus. Sixty-six participants, from Brunei, Kuala Lumpur, Johor, Kuching, Bintulu and Mukah took part in the competition. Among the objectives of staging the tournament were to promote UiTM Sarawak Mukah Campus to its highest level possible, to promote and uplift the Mini 4WD sports and to provide an avenue to foster closer rapport among participantsof the race. Other activities that took place simultaneously were the setting up of sales booths and exhibition booths as well as the organising of appealing indoor games by the students.